Optimizing the Queuing System at the Grogol Sukoharjo District Health Center Using the Line Balancing Method - Pebriyanto, Rahmat; Agusti, Febrina; Ismoyo Buwono, Ringgo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The average number of patients served by the Grogol Health Center in the general polyclinic is 40 to 45 patients every day. Based on these data, there is a buildup of 7-10 patients, with an average service time of 10 minutes per patient. From the results of further observations, there is a buildup of patients in the general polyclinic of the Grogol Health Center. This study aims to solve the queue problem with the line balancing method and develop an online registration application at the Grogol Health Center that can increase the efficiency of the patient registration process and reduce waiting time. Line Balancing is a method for solving queue system problems. So that the results of this study are the creation of an integrated application and online registration that can reduce waiting time